Camptothecin-PHA nanoparticles attenuate drug-induced gut microbiome dysbiosis and metabolic toxicity - Liu, Shanshuo; Rao, Benchen; Liu, Wenjie; Wang, Xuemei; Wang, Haiyu; Liu, Liwen; Zhang, Guizhen; Sun, Junyi; Li, Lei; Wei, Daixu; Yu, Zujiang; Ren, Zhigang (Frontiers in Microbiology, 2026)
IntroductionThe anticancer drug camptothecin (CPT) has limited clinical applications due to severe toxic reactions.MethodsWe combined CPT with PHBVHHx (PHA) nanoparticles by a modified emulsion method for the first time construct a novel nanomedical drug (CPT-PHA-NPs, CPNs).ResultsIn vitro experiments verified the drug loading level (89%), sustained-release properties (40% release within 48 h; near-complete release over 21 days), and inhibition ability of the compound on HT-29 cell activity (IC50 = 0.44 μM). In vivo, CPN-treated mice showed significantly less body weight reduction (P < 0.05 from day 7) and markedly improved liver and kidney function markers compared to controls. Histological analysis confirmed that CPN effectively prevented hepatocyte necrosis and renal inflammation observed with free CPT, demonstrating higher biosafety and lower toxicity. Crucially, 16S rRNA sequencing revealed that CPT severely depleted probiotics (Akkermansia, Lactobacillus, Candidatus_Arthromitus, and Bacilli_unclassified) while promoting pathogenic taxa (Lachnospiraceae_NK4A136_group, [Eubacterium]_xylanophilum_group, and Faecalibaculum), whereas CPNs attenuated these microbial disruptions. Metabolomics further showed CPNs' milder effects on phenylalanine and essential amino acid metabolism vs. CPT.DiscussionIn conclusion, this novel type of nanomaterial not only possesses excellent performance but also can reduce the impact of CPT on tissues, intestinal flora and serum metabolism, providing a new strategy for anti-tumor treatment that takes into account both microbial homeostasis and metabolic safety.